Common MRI findings in pre-signing medical assessments of professional soccer players - Höhne, E.; Mahmoudi, S.; Vogl, T.; Eichler, K.; Booz, C.; Bernatz, S.; Haser, C.; Plachel, F.; Pfab, F.; Yel, I. (BMJ Open Sport & Exercise Medicine, 2026)
Background/Aim In professional soccer, comprehensive musculoskeletal assessments are performed prior to player transfers to evaluate both the current condition and future risk of injury. MRI plays a crucial role in this process, effectively revealing musculoskeletal findings even in the absence of symptoms. This study presents common musculoskeletal MRI findings in professional soccer players undergoing pre-signing assessments and their associations with age, playing position and footedness.